EFEK KEFIR TERHADAP GAMBARAN HISTOLOGIS DAN KADAR MALONDIALDEHIDE HEPAR MENCIT PUTIH (MUS MUSCULUS) JANTAN GALUR BALB C DENGAN PAPARAN FORMALIN - Erna Susanti Ni Made Dwi Aryantini (Universitas Muhammadiyah Malang, 2012)
Kefir is a probiotic drink act as therapeutic agents in liver damage caused by exposure of formaldehyde. Therapeutic activities were estimate based on the content of kefir like antioxidants, lactic acid bacteria with yeasts, and essential amino acids. The purpose of this study was to prove the influence of kefir on the histological and levels of malondialdehyde (MDA) in liver of white mice (Mus musculus) male Balb C strain that exposure by formalin. The method used is experimental method, with three treatment groups, namely: (1) normal group, (2) the induction of formaline without kefir therapy group, (3) the induction of formaline with kefir therapy group. Histological of liver viewed by HE staining and MDA levels were measured by TBARS method. There are differences in the average number of significant cell damage induced by formalin group (p = 0030, p < 0.05). There are significant differences in MDA levels induced by formalin group (p = 0023, p < 0.05). These results are based on the ability of vitamin C, E and carotene (antioxidant) against Reactive Oxygen Species (ROS) due to exposure of formaldehyde, thus preventing the MDA levels increasing. Lactic acid bacteria and yeasts can preclude the possibility of healthy cells to be attacked by ROS with increasing the body’s immunity. Essential amino acids can repairing damaged cells by stimulating cell regeneration. It can be concluded that kefir with a dose of 107 CFU / ml act as therapeutic agents in liver damage due to exposure to formaldehyde.